1995
DOI: 10.1038/375331a0
|View full text |Cite
|
Sign up to set email alerts
|

Soluble antigen can cause enhanced apoptosis of germinal-centre B cells

Abstract: Germinal centres are dynamic microenvironments of B-lymphocyte differentiation, which develop in secondary lymphoid tissues during immune responses. Within germinal centres, activated B lymphocytes proliferate and point mutations are rapidly introduced into the genes encoding their immunoglobulin receptors. As a result, new specificities of B cells are created, including those with a heightened capacity to bind the immunizing antigen. Immunoglobulin gene mutation can also lead to reactivity to self antigens. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
165
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(175 citation statements)
references
References 30 publications
10
165
0
Order By: Relevance
“…In the bcl-2-Tg mice used in the present study, the Bcl-2 protein is expressed in B cells of the germinal center [28], and these Tg B cells are thus protected, though not completely, from apoptotic death following high-affinity interaction with their corresponding antigen [29]. It has also been shown that autoreactive anti-DNA B cells generated through somatic hypermutations are rescued as a result of the overexpression of the bcl-2 transgene [30].…”
Section: Discussionmentioning
confidence: 72%
“…In the bcl-2-Tg mice used in the present study, the Bcl-2 protein is expressed in B cells of the germinal center [28], and these Tg B cells are thus protected, though not completely, from apoptotic death following high-affinity interaction with their corresponding antigen [29]. It has also been shown that autoreactive anti-DNA B cells generated through somatic hypermutations are rescued as a result of the overexpression of the bcl-2 transgene [30].…”
Section: Discussionmentioning
confidence: 72%
“…In this version of the Tilman model populations grow in response to resources following a Monod (saturating) growth function that plateaus to a maximum for large amounts of resource. For antigen there is evidence to suggest that too much antigen is detrimental to the survival of peripheral B cells (18,19) so that the curve describing the peripheral net growth rate in response to resources may fall off from its peak value as antigen concentrations exceed their optimum level. We also would like to know about the production and decay characteristics of each resource (a and S) and finally about the consumption of resources by B cells (g).…”
Section: Models Of Resource Competition With Immigrationmentioning
confidence: 99%
“…If the Ag is present in the bone marrow, newly generated B cells can be deleted (7), rendered anergic (8 -11), or subjected to receptor editing (12,13). In contrast, if these high affinity B cells encounter the autoantigen in the periphery, they are deleted (14,15). Murine models expressing tg BCR with moderate affinity for soluble autoantigens were also studied in the case of rheumatoid factors (RF) (16) and single-stranded DNA (11); the models indicated that anergy is the main tolerance mechanism.…”
mentioning
confidence: 99%